A Comparative Study On Perceived Accident Risk Among The Cyclists, Motorcyclists And Drivers In The Mixed Traffic - Lim, Kai Jet (Universiti Sains Malaysia, 2022)
In Malaysia, motorcycles are a common mode of transportation, while cycling has recently had a resurgence in popularity, primarily as a form of recreation and sport. Road accidents happen often in Malaysia and are getting worse every year. This study investigates risk perceptions among cyclists, motorcyclists, and drivers in order to develop and implement mitigation strategies to improve road safety for cyclists, motorcyclists, and drivers in mixed traffic in Malaysia, with the aim of reducing the accident rate. The focus of this study was on working drivers and motorcyclists as well as recreational cyclists in Penang. Through a questionnaire, demographic data and self-reported risk perception were collected. Statistical Product and Service Solution (SPSS) was utilized to perform the statistical analysis. This research evaluated the significant difference in risk perception between cyclists, motorcyclists, and drivers. Although there is a significant difference in the socio demographic, experience, and characteristics of travel for drivers, motorcyclists, and cyclists, only 3 variables out of 16 self-reported perceived risks are significant differences, which are: the respondents have no problem adapting their driving, riding, or cycling to road surface conditions; the respondents can be lost in their thoughts when driving, riding, or cycling; and the presence of someone with the respondents in the car or on the motorcycle or behind them distracts them and deteriorates their driving, riding, or cycling. There is only 1 variable out of 3 self-reported perceived risks towards other road users that has a significant difference, which is among the drivers and the cyclists that they will reduce their speed when they see motorcycles on the road.